THE RELATIONSHIP BETWEEN MATERNAL DIETARY DIVERSITY SCORE DURING PREGNANCY AND INFANT NUTRITIONAL OUTCOMES: A LITERATURE REVIEW - Izmi Arisa Putri Lubis; Ray Wagiu Basrowi; Febriansyah Darus; Hindah Muaris (PT. Varians Statistik Kesehatan, 2026)
Background: Maternal nutrition during pregnancy is crucial for fetal development and long-term infant health. Dietary diversity is commonly used as an indicator of diet quality, reflecting the adequacy of macro-and micronutrient intake. This study aimed to examine the association between the Maternal Dietary Diversity Score (MDDS) during pregnancy and infant health outcomes.Methods:This study was a systematic literature review of 11articles. This article wassourced from scientific journal articles on Google Scholar, ScienceDirect, and PubMed for original observational studies published between 2015 and 2025.Results:The majority of research was carried out utilizing cohort, cross-sectional, or case-control designs in developing nations in Asia and Africa. Research continuously shows that a more varied diet for mothers is linked to better birth outcomes, especially higher birth weight and a lower chance of low birth weight (LBW). Additionally, a number of studies found that babies born to mothers who varied their diets were less likely to have low birth weights. Conclusions:MDDS is crucial for preventing LBWand supporting the baby's long-term growth and immunity. The quality of food choices and focused nutrition education are equally as important as the quantity of food groups